1995
DOI: 10.1016/0896-6273(95)90145-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gephyrin binding motif on the glycine receptor β subunit

Abstract: The tubulin-binding protein gephyrin copurifies with the inhibitory glycine receptor (GlyR) and is essential for its postsynaptic localization. Here we have analyzed the interaction between the GlyR and recombinant gephyrin and identified a gephyrin binding site in the cytoplasmic loop between the third and fourth transmembrane segments of the beta subunit. GlyR alpha subunits and GABAA receptor proteins failed to bind recombinant gephyrin. However, insertion of an 18 residue segment of the GlyR beta subunit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
358
2
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 394 publications
(378 citation statements)
references
References 41 publications
16
358
2
2
Order By: Relevance
“…Nevertheless, the functional differences reported by Ramirez-Latorre et al make in vivo receptor structure an important question. In addition to its possible effects on channel function, it is possible that the ␤3 subunit confers other properties on the receptor unrelated to channel function but more related to synaptic localization analogous to what has been observed for certain NMDA receptor (Ehlers et al, 1995;Kornau et al, 1995) and glycine receptor subunits (Meyer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the functional differences reported by Ramirez-Latorre et al make in vivo receptor structure an important question. In addition to its possible effects on channel function, it is possible that the ␤3 subunit confers other properties on the receptor unrelated to channel function but more related to synaptic localization analogous to what has been observed for certain NMDA receptor (Ehlers et al, 1995;Kornau et al, 1995) and glycine receptor subunits (Meyer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…7 The cytoplasmic loop of the GlyR β-subunit was later shown to bind to the E domain dimerization interface of gephyrin. 49,50 Coexpression of GlyR with gephyrin was found to change the ligand-binding affinities of human embryonic kidney 293 cells. 51 Treatment of rat spinal neurons with gephyrin antisense oligonucleotides was shown to block the formation of GlyR clusters in the neuronal membrane, suggesting that gephyrin is required to anchor GlyR in postsynaptic membrane specializations.…”
Section: Glyr β-Subunitmentioning
confidence: 99%
“…Initial cross-linking studies using puriWed spinal cord GlyR suggested that the receptor forms a pentamer with a deduced stoichiometry of three and two subunits and that the subunit was not involved in ligand binding (Langosch et al 1988;Laube et al 2002). Through its long intracellular loop between TM3 and TM4, the subunit can bind to gephyrin (Kim et al 2006;Meyer et al 1995;Sola et al 2004), thereby enabling the formation GlyR aggregations linked to subsynaptic protein scaVolds. However, the gephyrin scaVold (see below) is believed to provide three binding sites for GlyR subunits (Schrader et al 2004).…”
Section: Postsynaptic Membrane Specializationmentioning
confidence: 99%
“…It was hypothesized that this protein could form a bridge between the GlyR and the underlying microtubular cytoskeleton and therefore named gephyrin ( ; Greek: bridge) upon elucidation of its primary structure (Prior et al 1992). Gephyrin can interact with a short sequence motif (18 amino acids) within the large cytoplasmic loop of the GlyR subunit thereby establishing a direct, continuous molecular link between hetero-oligomeric GlyRs and gephyrin Kneussel et al 1999b;Meyer et al 1995). The known GlyR subunits and many GABA A receptors did not bind gephyrin in a cellular assay .…”
Section: Anchoring and Traycking Of Glyrmentioning
confidence: 99%
See 1 more Smart Citation